2002
DOI: 10.1007/s00441-002-0566-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and glial localization of GABA transporter immunoreactivity in the myenteric plexus

Abstract: The neurotransmitter gamma-aminobutyric acid (GABA) is removed from the extracellular space by sodium and chloride dependent high affinity plasma membrane transporters. In the rat central nervous system, three GABA transporters, GAT1, GAT2 and GAT3, have been cloned and localized by immunohistochemistry. The purpose of this study was to examine the distribution of these transporters within the myenteric plexus of the rat gastrointestinal tract. We investigated their cellular locations using GAT1-3 specific ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
0
40
0
1
Order By: Relevance
“…It is known that there is a characteristic distribution of GABA transporters across different regions. In the myenteric plexus, it was reported that GAT-2 is expressed in glial cells and GAT-3 is expressed in neurons (Fletcher et al 2002). In the central nervous system, GAT-1 and GAT-3 are expressed abundantly, and GAT-1 is expressed in neurons and, to some degree, in astrocytes, whereas GAT-3 is the predominant GABA transporter within astrocytes (Barbaresi et al 2001;Minelli et al 1996).…”
Section: Effect Of Endogenous Gaba In Ngmentioning
confidence: 99%
“…It is known that there is a characteristic distribution of GABA transporters across different regions. In the myenteric plexus, it was reported that GAT-2 is expressed in glial cells and GAT-3 is expressed in neurons (Fletcher et al 2002). In the central nervous system, GAT-1 and GAT-3 are expressed abundantly, and GAT-1 is expressed in neurons and, to some degree, in astrocytes, whereas GAT-3 is the predominant GABA transporter within astrocytes (Barbaresi et al 2001;Minelli et al 1996).…”
Section: Effect Of Endogenous Gaba In Ngmentioning
confidence: 99%
“…Indeed, enteric glia release neurotransmitters in vitro (Zhang et al, 2003), express receptors (Kimball and Mulholland, 1996;Nasser et al, 2006b;Van Nassauw et al, 2006;Vanderwinden et al, 2003;von Boyen et al, 2006), biosynthetic enzymes (Jessen and Mirsky, 1983) as well as reuptake transporters (Fletcher et al, 2002;Ruhl et al, 2005) for neurotransmitters. Functional disruption of enteric glia causes subtle changes in intestinal motility (Aube, 2005;Nasser et al, 2006a), suggesting that these cells modulate enteric neural signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Most EGC within enteric ganglia are contacted by vesiculated nerve processes with presynaptic specializations [35], and respond to transmitters released by these terminations by expressing a series of receptors for neurotransmitters and neuromodulators [36][37][38][39]. Thus, EGC can modulate enteric neural circuits in several ways, such as by supplying neurotransmitters precursors to neurons [40,41], terminating the actions of neurotransmitters from synapses [42,43], and through the generation of neuroactive compounds [44]. In addition, EGC are needed to assure survival of the enteric neurons, as demonstrated by the experimental ablation of the intestinal glial network [45].…”
Section: Interlinks Of Enteric Glial Cells With Enteric Neurons and Nmentioning
confidence: 99%